“ANALYSIS OF STRATEGIES FOR TEACHING VOCABULARY IN THE TEACHING –LEARNING PROCESS OF ENGLISH FOR ACADEMIC PURPOSES (AUTOMOTIVE MECHANICS) WITH THE STUDENTS AT PRIMERO DE BACHILLERATO “A” OF UNIDAD EDUCATIVA “CARLOS CISNEROS” IN THE CITY OF RIOBAMBA CHIMBORAZO PROVINCE IN THE ACADEMIC YEAR 2017-2018” - Santos Layedra, Brayan Sebastián (2019)
The inappropriate application of strategies to teach technical vocabulary (mechanical automotive) in the students of Primero de Bachillerato “A” at Unidad Educativa “Carlos Cisneros” during the academic term 2018-2019 was established as a problem. It was evident during the observation that the students did not know many English words referring to their technical formation due to the inappropriate application of the strategies to teach this kind of vocabulary. The purpose of this research is to analyze the strategies to teach technical vocabulary. The observed population was 38 students. This study was qualitative because the information collected by a non-participative observation that was used served for the subsequent interpretation of results, the instrument was an observation guide created by the researcher. It was determined after the interpretation of data that the teacher focuses on the basic English, the technical English left behind, it was also concluded that the teacher had at least 4 strategies to teach vocabulary, from which the was STAR Model of Direct Instruction was feasible to teach technical vocabulary.